2022
DOI: 10.1029/2022jc018591
|View full text |Cite
|
Sign up to set email alerts
|

Biomineral Flocculation of Kaolinite and Microalgae: Laboratory Experiments and Stochastic Modeling

Abstract: The transportation of cohesive sediments has attracted great attention for decades due to the significant influences of sediments on various coastal and offshore engineering (e.g., siltation, dredging, seawall foundation treatment, and riverbed morphology) and environmental (e.g., pollutant transport, phytoplankton photosynthesis, and coastal wetland sustainability) issues (Coats et al., 1989;Edmonds & Slingerland, 2010;Sun et al., 2021;Teisson, 1991). It is a challenge to precisely predict the dynamic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Using similar materials and the experimental setup, Zhu et al. (2017, 2022) observed that the viscosities of kaolinite suspensions exhibited the same trend of increasing and then reaching a plateau with sediment volume concentration. Nevertheless, some differences in absolute viscosity values were observed between their findings and those of this study, which may be attributed to the variances in sediment size, and/or sample preparation, and/or experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using similar materials and the experimental setup, Zhu et al. (2017, 2022) observed that the viscosities of kaolinite suspensions exhibited the same trend of increasing and then reaching a plateau with sediment volume concentration. Nevertheless, some differences in absolute viscosity values were observed between their findings and those of this study, which may be attributed to the variances in sediment size, and/or sample preparation, and/or experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…These organic matters can interact with sediment particles and flocs, potentially altering their structural properties and thus influence the rheological properties of the flow. It is widely known that organic matter can act as a biological glue that facilitate flocculation and promote the formation of biofilm, which consists of microbial communities embedded in EPS, can further modify sediment properties (Deng et al., 2019; Droppo, 2009; Fettweis et al., 2022; Zhu et al., 2022). In particular circumstance such as in the environment abundant of biomass (e.g., wetland, tidal creek, and mangrove area) or during the algal bloom period, the biological effects may become the significant factor influencing flocculation and the rheological behavior of the sediment‐water mixture compared to the hydrodynamic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation